Assessment of haematological parameters in HIV-infected and uninfected Rwandan women: a cross-sectional study. Issue 6 (20th November 2012) - Munyazesa, Elisaphane; Emile, Ivan; Mutimura, Eugene; Hoover, Donald R; Shi, Qiuhu; McGinn, Aileen P; Musiime, Stephenson; Muhairwe, Fred; Rutagengwa, Alfred; Dusingize, Jean Claude; Anastos, Kathryn
Abstract : Objectives: Although haematological abnormalities are common manifestations of HIV infection, few studies on haematological parameters in HIV-infected persons have been undertaken in sub-Saharan Africa. The authors assessed factors associated with haematological parameters in HIV-infected antiretroviral-naïve and HIV-uninfected Rwandan women. Study design: Cross-sectional analysis of a longitudinal cohort. Setting: Community-based women's associations. Participants: 710 HIV-infected (HIV+) antiretroviral-naïve and 226 HIV-uninfected (HIV−) women from the Rwanda Women's Interassociation Study Assessment. Haematological parameters categorised as (abnormal vs normal) were compared by HIV status and among HIV+ women by CD4 count category using proportions. Multivariate logistic regression models using forward selection were fit. Results: Prevalence of anaemia (haemoglobin (Hb) <12.0 g/dl) was higher in the HIV+ group (20.5% vs 6.3%; p<0.001), and increased with lower CD4 counts: ≥350 (7.6%), 200–349 (16%) and <200 cells/mm 3 (32.2%). Marked anaemia (Hb <10.0 g/dl) was found in 4.2% of HIV+ and none of the HIV− women (p<0.001), and was highest in HIV+ women with CD4 <200 cells/mm 3 (8.4%). The HIV+ were more likely than HIV− women (4.2 vs 0.5%, respectively, p=0.002) to have moderate neutropenia with white blood cells <2.0×10 3 cells/mm 3 and 8.4% of HIV+ women with CD4 <200 cells/mm 3 had moderate neutropenia. In multivariate logistic regression analysis, BMI (OR 0.87/kg/m 2, 95% CI 0.82 to 0.93; p<0.001), CD4 200–350 vs HIV− (OR 3.59, 95% CI 1.89 to 6.83; p<0.001) and CD4 <200 cells/mm 3 vs HIV− (OR 8.09, 95% CI 4.37 to 14.97; <0.001) had large independent associations with anaemia. There were large independent associations of CD4 <200 cells/mm 3 vs HIV− (OR 7.18, 95% CI 0.78 to 65.82; p=0.081) and co-trimoxazole and/or dapsone use (OR 5.69, 95% CI 0.63 to 51.45; p=0.122) with moderate neutropenia. Conclusions: Anaemia was more common than neutropenia or thrombocytopenia in the HIV-infected Rwandan women. Future comparisons of haematological parameters in HIV-infected patients before and after antiretroviral therapy initiation are warranted.